Новий Остерський замок. Нарис з історії оборони та топографії фортифікацій - Ігнатенко, І. (Сiверянський літопис, 2020)
У статті порушені питання топографії та бойовій історії фортифікацій Нового Остра. Місто Остер, що виникло у ХІ ст. на березі однойменної річки при впадінні її в Десну, в ХІІ ст. вже мало три лінії оборонних укріплень, рештки яких зберігалися до середини ХХ ст. У 60-х рр. ХVІ ст. Остерський замок та поселення навколо нього були перенесені на нове місце, що пов'язано зі зміщенням русла Десни. На той момент Остер був замком Речі Посполитої на кордоні з Великим князівством Московським. На підставі описів ХVІ–ХVІІ ст. автор реконструював місцезнаходження замку Нового Остра. Після спалення міста та замку московитами у 1616 р. остерський староста Єреміан Залеський почав відновлювати поселення біля старого городища. Однак уряд Речі Посполитої не підтримав цього проекту й наказав відбудувати замок на місці Нового Остра, щоб місцевий гарнізон міг контролювати перевезення Десною. Для приваблення людей та поліпшення економічного стану поселення у 1628 р. уряд Речі Посполитої звільнив жителів Нового Остра від сплати податків спочатку на 8 років, а потім ще на 6 років. Внаслідок цього поселення помітно виросло. У середині ХVІІ ст. Новий Остер мав замок, укріплений дерев'яними стінами та вежами, та дві лінії оборонних укріплень навколо міської забудови. Фортифікації прикривали місто зі сходу, з інших сторін місто мало природний захист – ріки Попівку та Десну й озеро Деснище. У ході російсько-української війни 1668 р. вздовж річки Попівки від замку, зайнятого московськими ратними людьми, також були споруджені оборонні укріплення. Після другого поділу Польщі у 1793 р. західний кордон Російської імперії сильно відсунувся на захід, відтак фортеця в Острі стала непотрібною й була розібрана. The article is devoted to the study of the battle history of the new town of Oster and the topography of its fortifications. The fortress of Oster originated in the 11th century on the bank of the river of the same name, at its confluence with the river Desna, in the 12th c. settlement already had three lines of fortifications, the remains of which remained until the mid-20th century. In the 60’s 16th c. Oster Castle and the surrounding settlements were rebuilt in a new location due to the displacement of the Desna River bed. At that time, Oster was the castle of the Commonwealth on the
border with the Grand Duchy of Moscow. Based on the descriptions of the 16th and 17th centuries, the author reconstructed the location of the castle of new Oster. After the town and the castle were burned down by the Muscovites in 1616, the Osterian governor Remigian Zaleski began to rebuild the settlement near the old hillfort.However, the government of the Polish-Lithuanian Commonwealth did not support this project, and ordered the castle to be rebuilt on the site of New Oster so that the local garrison could control traffic along the Desna River. In order to attract people to the town and improve its economic status, in 1628 the Polish-Lithuanian Commonwealth government released the residents of new Oster from paying taxes, first for 8 years and then for another 6 years. As a result, the settlement has grown significantly. In the mid-17th century. New Oster had a castle, fortified with wooden walls and towers, and two lines of defensive fortifications around the town. Fortifications defended the city from the east, on the other hand the city had a natural protection – the Popivka and Desna rivers and Lake Desnishche.During the Russo-Ukrainian War of 1668, fortifications were built along the river Popivka, which were to defense the town from the castle occupied by Moscow soldiers. After the second partition of Poland in 1793, the western border of the Russian Empire moved much westward, so the fortress in Oster became unnecessary and was dismantled.